Implementasi Materi Tasawuf pada Siswa Madrasah Aliyah Negeri (MAN) Karaanganyar Tahun Ajaran 2015/2016 - Wardani, Fitria Kusuma; , Dr. Badaruddin, M.Ag; , Dr. Mutohharun Jinan, M.Ag (2017)
Education aims at educating the nation and developed a complete Indonesian man, the man who is faithful and devoted to God Almighty and virtuous, have the knowledge and skills, physical and spiritual health, personality and former self, and sense of responsibility of community and nationality , Education laden soul divine soul offered al-Farabi for an educator, comes down to the mental potential, which is not only smart on the intellectual aspects (cognitive), but the emphasis was on how to apply and integrate science in society is increasing good deeds. MAN Karanganyar students should have good morals. Respect the teacher, always work on a job, praying in an orderly manner, and does not violate the discipline that has been set. Facts on the ground shows many students of MAN Karanganyar who can not change his life, many students do even juvenile delinquency in the school environment. Often they break school rules. Issues to be raised is "how the implementation of Sufism material on students grade XI MAN Karanganyar 2015/2016 school year? What are the factors supporting and inhibiting? "The purpose of this study is to investigate the implementation of the material in class XI student of Sufism MAN Karanganyar 2015/2016 school year. This kind of research is a field research, study was conducted directly in the field, namely in MAN Karanganyar to obtain the necessary data. The subject of this research is the students of class XI MAN Karanganyar the academic year 2015/2016. Samples from three class containing 120 students, then 10% of 120 is 12 students. Data collection technique used interview and observation. Technique authenticity of data using data reduction, data presentation, drawing conclusion / verification. The results of this study indicate that Sufism learning process goes well, using the Active Learning and teaching methods adequate learning media. Most students of class XI Karanganyar MAN has been unable to implement Sufism material well, at school and at home. It was concluded that the learning process has been implement Sufism well but most of the students had been unable to implement the values of Sufism in everyday life. Keywords: Education; Learning; Sufism.